Correction: In solution SERS sensing using mesoporous silica-coated gold nanorods. Issue 24 (21st November 2016) - Gao, Zhe; Burrows, Nathan D.; Valley, Nicholas A.; Egger, Sam; Schatz, George C.; Murphy, Catherine J.; Haynes, Christy L.
Abstract : Correction for 'In solution SERS sensing using mesoporous silica-coated gold nanorods' by Zhe Gao, et al., Analyst, 2016, 141, 5088–5095.